2004
DOI: 10.1002/gps.1027
|View full text |Cite
|
Sign up to set email alerts
|

Poor mental and physical health differentially contributes to disability in hospitalized geriatric patients of different ages

Abstract: Functional disability after acute hospitalization is highly prevalent in geriatric patients. Depressive symptoms, comorbidity, and cognitive impairment often coexist, interact and are differentially associated with function depending on age. Considering that depressive symptoms are a modifiable problem, their detection in hospital settings may help clinicians in targeting subjects at high risk of functional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…Interestingly, a recent prospective study indicates that a more severe impairment in executive function at baseline examination significantly predicts a faster IADL decline in the elderly either with or without cognitive impairment (Cahn-Weiner et al, 2007). Lastly, our findings support the hypothesis that with aging there is a hierarchy of functional loss in which mild cognitive decline primarily affects performances in IADL activities (Njegovan et al, 2001;Aguero Torres et al, 2002) whereas a more severe cognitive impairment and somatic disorders interact in affecting BADL (Marengoni et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, a recent prospective study indicates that a more severe impairment in executive function at baseline examination significantly predicts a faster IADL decline in the elderly either with or without cognitive impairment (Cahn-Weiner et al, 2007). Lastly, our findings support the hypothesis that with aging there is a hierarchy of functional loss in which mild cognitive decline primarily affects performances in IADL activities (Njegovan et al, 2001;Aguero Torres et al, 2002) whereas a more severe cognitive impairment and somatic disorders interact in affecting BADL (Marengoni et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…The association between the period of time living in the long-term care facility and the deterioration in cognitive and functional abilities has been previously reported [60,61]. Furthermore, higher severity of cognitive impairment was linked with increased disability in activities and participation [62,63]. Therefore, the negative correlation found between WHODAS 2.0 and MMSE total scores confirmed that as the cognitive status deteriorates, the limitation in activities and restriction in participation increases [6,9,50,62,63].…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, higher severity of cognitive impairment was linked with increased disability in activities and participation [62,63]. Therefore, the negative correlation found between WHODAS 2.0 and MMSE total scores confirmed that as the cognitive status deteriorates, the limitation in activities and restriction in participation increases [6,9,50,62,63]. This is an important result for rehabilitation, since it suggests that maintaining people with dementia involved in activities and participation could be a protective factor to delay cognitive decline [64,65].…”
Section: Discussionsupporting
confidence: 65%
“…Cognitive impairment is also often used as a predictor of poorer hospitalization outcomes but without taking into account comorbid medical conditions, functional and nutritional status (Bertozzi et al, 1996;Inouye et al, 1998;Di Iorio et al, 1999;Fogel et al, 2000;Marengoni et al, 2004;Lang et al, 2006). In addition, in most of these studies, 'cognitive impairment' was defined based on MMSE score alone, with no accurate diagnosis of dementia, its etiology and severity (Folstein et al, 1975).…”
Section: Introductionmentioning
confidence: 98%